Daripada Jawi peranakan kepada Melayu: tinjauan terhadap komuniti Jawi peranakan di Pulau Pinang pada abad ke-21 - Omar Yusoff,; Noriah Mohamed, (Universiti Kebangsaan Malaysia, 2010)
This paper will review the Jawi Peranakan community that settled in Penang. A survey was conducted through qualitative methods and focused on library research and non-structured interviews between the researcher and the Jawi Peranakan informants. This survey found that the arrival of the immigrants and traders from India and Arab to Penang gave rise to the Jawi Peranakan community through inter-marriage between these groups with local Malay women. The hybrid group was originally known as Jawi Pekan, nevertheless later it was addressed as Jawi Peranakan. At present, the Jawi Peranakan was inclined to adopt Malay culture and in the process to become Malay, the process of assimilation and amalgamation experienced by these peoples over the years had caused most of them no longer maintain their culture because it is said to be contrary among Muslims. Shift not only occurred on the cultural aspects, but the language aspect also exhibits the same condition. This paper will describe and explore current changes in culture and language of Jawi Peranakan in Penang